Perception of Public Relations Officers of Government Public Relations Approaches towards the Acceptability of COVID-19 Vaccination in Taraba State, Nigeria - Gbaden, Chiakaan Jacob; Faith, Bamigboye Damilola (Darul Yasin Al Sys, 2024)
This study on perception of public relations officers on government public relations approaches towards the acceptability of Covid 19 vaccination in Taraba State, Nigeria sought to identify the public relations approaches adopted by government in the campaign for COVID-19 vaccine, examine public relations experts perception of the impact of public relations approaches in the campaign for COVID-19 vaccine in Taraba State, Nigeria and to find out the specific challenges faced by the public relations experts in the campaign for COVID-19 vaccine in Taraba State, Nigeria. The study employed the survey method of research design with a population of 158 and a sample. Using purposive sampling method, questionnaires was administered on a sample size of 103 respondents within the study area to elicit primary data. Findings of the study revealed that the government in Taraba State has implemented a diverse range of public relations (PR) strategies to promote the Covid-19 vaccine campaign. The study also found that public relations experts generally perceive the government's PR approaches positively. Furthermore, the study revealed that despite the overall positive perception of the PR efforts, several challenges persist such as vaccine hesitancy, limited access to reliable information sources and insufficient resources and funding key hurdles faced. The study concluded that the government's adoption of diverse PR strategies, including communication campaigns, media relations efforts, and collaboration with healthcare providers, demonstrates a proactive effort to engage with the public and address concerns. Finally, the study among others recommended that community engagement through grassroots initiatives, involving local influencers, community leaders, and healthcare providers and advocate for increased resources and funding to support comprehensive PR campaigns should be enhanced.